Erwinia plantamica sp. nov., a Non-Phytopathogenic Bacterium Isolated from the Seedlings of Spring Wheat (Triticum aestivum L.) - Anna Egorshina; Mikhail Lukyantsev; Sergey Golubev; Eugenia Boulygina; Irina Khilyas; Anna Muratova (Microorganisms)
Erwinia are widely known as phytopathogenic bacteria, but among them, there are also plant-friendly strains that can promote plant growth (PGPR). The Erwinia-like strain OPT-41 was isolated from Triticum aestivum seedlings as a potential PGPR. The cells (0.9–1.3 × 1.5–3.1 µm) of this microorganism are Gram-negative, rod-shaped, motile (with peritrichous flagella), and non-spore- and non-capsule-forming. The 16S rRNA gene sequence analyses showed it is located in the Erwiniaceae family and has a pairwise similarity above the species delineation threshold of 98.65% with several of its members: Erwinia tasmaniensis (99.21%), Candidatus Pantoea bathycoeliae (98.93%), Pantoea agglomerans (98.87%), Erwinia endophytica (98.83%), Erwinia persicina (98.82%), Erwinia billingiae (98.76%) and Erwinia aphidicola (98.75%). Whole genome-based taxonomy performed on the Type (Strain) Genome Server clarified the status of strain OPT-41, detecting it as a potential new species in the genus Erwinia. The microorganism under study was the most closely related to the type strain of E. phyllosphaerae, demonstrating 27.2% similarity in dDDH, 83.44% similarity in OrthoANIu, and 1.9% difference in G+C content. The major fatty acids of strain OPT-41 were 9 C16:1, C14:0, and C16:0. A combination of genome-based taxonomy and traditional polyphasic taxonomy clearly indicated that strain OPT-41 belongs to a novel Erwinia species, for which the name E. plantamica sp. nov was proposed. OPT-41 (=IBPPM 712=VKM B-3873D=CCTCC AB 2024361) has been designated as the type strain. In addition, OPT-41 was found to have low degradation potential for host plant pectins and proteins and be friendly in Triticum aestivum and Hordeum vulgare crops.